(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2023)
Wildlife sanctuaries – formally designated protected areas managing populations of threatened or charismatic megafauna – generate diverse ecosystem services beyond biodiversity conservation, including carbon sequestration, watershed regulation, pollination support, cultural services, and direct economic contributions through ecotourism, yet these services remain systematically undervalued in national accounts and conservation investment decisions relative to the opportunity costs of protection. This study conducted a comprehensive ecosystem services valuation (ESV) of 18 European wildlife sanctuaries across five biome types (Mediterranean shrubland, temperate deciduous forest, alpine grassland, boreal forest, Atlantic coastal wetland) using a multi-method valuation framework integrating market price methods, benefit transfer, contingent valuation (n = 2,842 respondents), and biophysical modelling (InVEST). Total estimated economic value across all 18 sanctuaries was EUR 2.84 billion annually, comprising carbon sequestration (31.2%), ecotourism (28.4%), watershed services (18.4%), biodiversity option value (12.4%), pollination (5.4%), and cultural/existence values (4.2%). Per-hectare annual ESV ranged from EUR 842 (boreal forest; low ecotourism, high carbon) to EUR 4,284 (Atlantic coastal wetland; high fisheries support and watershed services). Willingness-to-pay (WTP) for sanctuary conservation among surveyed residents was EUR 48.4 +- 24.8/year per household (contingent valuation; n = 2,842), aggregating to a total WTP of EUR 284 million across the survey catchment area. Benefit-cost analysis confirmed positive net present value (NPV) for sanctuary conservation in all 18 cases (mean benefit-cost ratio BCR = 4.84 +- 1.84), with the highest BCR in Atlantic coastal wetlands (BCR = 7.84) driven by high fisheries support and carbon co-benefits. These results provide an evidence base for sanctuary conservation investment under the EU Biodiversity Strategy 2030 payment for ecosystem services framework.